IMPLEMENTASI FUZZY TAHANI DALAM PENENTUAN PEMBELIAN SMARTPHONE - Wahyu Dwi Prasetio; Astuti Zahrroh; Abdul Khudri Barkah Rizki; Achmad Rilwanul Izzati; Danny Brantadikara; Widhia Oktoeberza KZ (Teknosia, 2022)
In 2021, 65.87% of the Indonesian population had a mobile phone. The smartphone market in Indonesia is expected to increase by 8% from the previous year to 44 million units in 2022. Users must consider various factors such as price, specifications, and others before deciding to buy a smartphone. In an effort to develop a smartphone selection support system, research uses the Fuzzy Tahani method. The Fuzzy inference system model Tahani will process the input provided by the user and then return the processed result as an output list of smartphone recommendations to the user sorted by fire strength value. As a final result, the fuzzy logic Tahani model can be used to provide accurate smartphone selection recommendations by considering various criteria proportionally.